(untitled) (Psychology Travelogs, 2025)
The question of the origin of the «self» – the inner subject that is aware of itself – remains insufficiently explored, especially from the perspective of historical development. As early as antiquity, philosophers raised questions about the nature of thought, self-knowledge, and inner reflection. In Christian philosophy, the focus shifts toward spiritual self-understanding. The Renaissance proclaims the dignity and freedom of the individual, capable of shaping himself independently. For the first time, the human being becomes aware of himself as an autonomous subject. In the Early Modern Period, the idea of the «self» emerges as the foundation of knowledge. Thus, the idea of the «self» was shaped over centuries – in philosophy, religion, and eventually psychological science – as a key category of human experience.